Verbe de l'amour? Le verbe païr dans deux textes occitans - Majorossy, Imre Gábor (Verbum – Analecta Neolatina, 2004)
The following study shows metaphorical meanings of a verb (païr) that comes from the religious tradition. Two texts will be presented: a poem of Raimbaut d'Aurenga and an occitan short story. Both speak about love and both use païr in a somewhat unusual way. In the poem, païr expresses love of the Domna; in the short story, after their marriage, lovers take new names and the wife has one that contains païr. The study tries to reveal a possible literary relationship between semantic fields of païr and aimer.